Pirinola City: Design of material to reinforce lexical competence in English through oral production via Gamification for eleventh grade students at Almirante Padilla School (2024)
This degree project focuses on addressing the problem of low lexical proficiency in English among four (4) eleventh grade students at Colegio Almirante Padilla. In the institution, it is recognized that the lack of adequate teaching resources and the absence of effective pedagogical strategies are significant barriers to learning English in this educational context.